2001
DOI: 10.1084/jem.193.10.1135
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Parasite-Derived Prostaglandin D2 in the Inhibition of Epidermal Langerhans Cell Migration during Schistosomiasis Infection

Abstract: Epidermal Langerhans cells (LCs) play a key role in immune defense mechanisms and in numerous immunological disorders. In this report, we show that percutaneous infection of C57BL/6 mice with the helminth parasite Schistosoma mansoni leads to the activation of LCs but, surprisingly, to their retention in the epidermis. Moreover, using an experimental model of LC migration induced by tumor necrosis factor (TNF)-α, we show that parasites transiently impair the departure of LCs from the epidermis and their subseq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
242
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 251 publications
(247 citation statements)
references
References 56 publications
4
242
0
1
Order By: Relevance
“…During murine schistosomiasis, parasite-derived eicosanoids may play important roles in the cutaneous immune response [15,28]. Immunolabeling with highly specific Ab indicated that Sm28GST is massively excreted in the epidermis of infected mice ( Fig.…”
Section: Sm28gst Inhibits the Migration Of Lc From The Epidermis To Tmentioning
confidence: 99%
See 2 more Smart Citations
“…During murine schistosomiasis, parasite-derived eicosanoids may play important roles in the cutaneous immune response [15,28]. Immunolabeling with highly specific Ab indicated that Sm28GST is massively excreted in the epidermis of infected mice ( Fig.…”
Section: Sm28gst Inhibits the Migration Of Lc From The Epidermis To Tmentioning
confidence: 99%
“…Since DP1 activation appears to be important in the control of LC motility in vivo [15], WT or DP1 KO mice were i.d. injected with rSm28GST before TNF- § treatment, and LC density was determined (Fig.…”
Section: Sm28gst Affects Lc Migration Through Dp1 Activationmentioning
confidence: 99%
See 1 more Smart Citation
“…We have reported that PGD 2 inhibits the migration of maturing DC via DP1 [9,14,15] whereas it increases the chemokinetic activity of DC precursors through DP2 [11]. Moreover, PGD 2 profoundly modulates the immunoregulatory capacity of DC via DP1 [11,16].…”
Section: Introductionmentioning
confidence: 97%
“…In addition to the genetic background, it is likely that the tissue environment also determines the capacity of DC to induce Th2 responses consecutively to allergen exposure. For instance, among the main mediators released early during the allergic reaction, histamine and PGD 2 are important for DC functions [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%